Application of remote real-time monitoring of biological airborne particles to characterise different hospital environments. Issue Volume 1(2019)Issue A (8th March 2019) - Fennelly, Mehael; O'Connor, David; Murphy, Noel; Casey, Colman; Plant, Barry; O'Sullivan, Niamh; Hellebust, Stig; Sodeau, John; Prentice, Mike
Abstract : Conventional microbial sampling of air in hospitals is usually carried out using settle plates or impaction air samples. This provides little information about intermittent contamination events and is unhelpful for source attribution. Direct continuous bioaerosol sampling is an established technology used to characterise ambient external air. Portable instruments such as the Wideband Integrated Bioaerosol Sensor (WIBS) combine laser particle size and shape detection with signals of biological origin (fluorescence from amino acids and NAD(P)H) characteristic of viable bioaerosols. Monitoring is continuous for weeks at a time and data collected remotely over the internet. We present evidence of the utility of WIBS analysis in characterising air in hospitals in three different environments: operating theatres (plenum ventilated and ultraclean), a respiratory ward, and a specialist cystic fibrosis outpatients. The airborne particle profile was quantitatively and qualitatively different in each environment. Plumes of biologically-relevant airborne particles were detected and source investigation of failing conventional counts in an operating theatre aided by the continuous record. Nebulised drugs contributed a detectable effect on airborne particles which lasted for several hours on the ward despite air changes. A significant effect of plasma air treatment on airborne particles in the ward was detected by WIBS and not conventional cultures. Continuous monitoring may in future allow objective standard setting for airborne particles in different hospital environments and facilitate rapid detection of airborne infection risks.